Serum Sialic Acids Levels According to the Severity of Liver Cirrhosis - Chrostek, Lech (J Clin Lab Anal, 2014)
BACKGROUND: The sialylation of serum proteins and lipids changes in liver diseases of different etiologies and could change the total sialic acid (TSA), lipid‐bound SA (LSA), and free SA (FSA) levels in the sera. However, little is known of the relationship of serum SAs concentrations and the severity of liver disease. Therefore, the aim of this study was to investigate the SAs concentrations (TSA, LSA, and FSA) in liver cirrhosis in relation with the severity of liver disease. METHODS: Tested group consisted of 91 consecutive patients suffering from liver cirrhosis. For each patient, the Child‐Pugh score was calculated. TSA and LSA were determined by the enzymatic method on microplate reader, and FSA using the thiobarbituric method. RESULTS: Among the SA forms, only the serum FSA level in liver cirrhosis appears to be different according to the severity of liver damage evaluated by the Child‐Pugh score. It was the highest in score C, and was higher than that in scores B and A. The elevated levels of FSA significantly positively correlated with the Child‐Pugh score. CONCLUSION: In conclusion, the sialylation of serum proteins and lipids changes in liver cirrhosis, but only the serum concentrations of FSA are stage‐related and reflect the severity of liver disease.